Assessment of Energy Use and Photovoltaic Energy Potential in Saudi Arabian Governmental Schools - Radwan A. Almasri; Ahmad Eid; A. F. Almarshoud; F. H. Almotairy (Applied Sciences, 2025)
Adopting photovoltaic (PV) systems in government schools across Saudi Arabia presents an opportunity to reduce energy costs and contribute to the country’s RE goals. In this paper, the energy consumption and energy consumption indicators of 3 schools in Qassim region (the central region of the Kingdom of Saudi Arabia) were determined. The integration of PV systems into the buildings of these schools was also studied to achieve zero energy and zero bills along the system’s life cycle. The analysis considered the effects of temperature and other factors on PV system output and a projected 1% annual increase in school load. Energy use intensity ranged from 22 to 48 kWh per square meter, while per capita energy use varied between 337 and 630 kWh. Values for end-use of electricity of 80%, 11%, and 9% were obtained for air conditioning, lighting, and others, respectively. The results note that the zero-energy scenario’s technical, economic, and environmental indicators are appropriate. The indicators in the zero-billing case were similar to the energy-zero scenario except for the payback period, which was longer and, in some cases, not economically feasible. The results show that economic evaluation must be revisited by reviewing the tariff value for selling surplus energy to the distribution network. The study also recommends scaling this model to other educational institutions, contributing to sustainable energy transitions in Saudi Arabia.